“Unleasing their power: young women who powerlift and attend a co-educational school in the Northern Suburbs” - Du Plessis, Adrienne Zendrea (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.